THE CONFLICTS OF THE MAIN CHARACTER IN THE NOVEL ENTITLED “STILL ALICE” BY LISA GENOVA - Pratami, Ayu Venty; Djohan, Rita Sutjiati; Purwaningsih, Endang (Universitas Gunadarma, 2016)
This study about the conflicts of the main character in the novel Still Alice. The main character in the novel Still Alice is Alice Howland. Alice Howland faces many conflicts with herself, her family and friends in the novel Still Alice. The Objectives of the research are to find out the types of conflict that occur on the main character in the novel Still Alice and to find out the type of conflict occurs dominantly in the novel Still Alice. The writer uses psychological approach for analyzing types of conflict in main character, Alice Howland in the novel Still Alice. The writer uses qualitative descriptive method to find out types of conflicts in main character in the novel Still Alice. The results of this study shows that Alice Howland has four types of conflict according to the of Kurt Lewin’s theory, As follows: Approach – Approach Conflict, Avoidance – Avoidance Conflict, Approach – Avoidance conflict, Double Approach – Avoidance Conflict and the type of conflict occurs dominantly in the novel Still Alice is the approach - avoidance conflict. Everyone always experience a lot of problems in their lives. Therefore, everyone should be able to resolve their problems by taking the best decision for them and other people in their problems.Keywords: Literature, Conflicts, Psychology